The impact of Agriculture productivity on economic growth in Brazil - Otabaev Yodgorbek Marim o’g’li (Zien Journals, 2024)
This study employes the time-series data analysis in terms of examining the impact of agriculture productivity on economic growth in case of Brazil throughout the period of 1973 and 2022. The outcomes of previous studies have been vary based on their empirical and theoretical approaches. The ARDL cointegration model is employed so as to interpret both short and long run relationships of independent variables with dependent variable. The outcome of this study suggested that, agriculture productivity is proposed to have negative impact on economic growth of concerned country in both short and long run relations. In addition to this, as a controlling variable some other variables are involved such as Inflation, gross capital formation, labor force and trade openness, the impact factor of those variables are also provided in the further paragraphs deeply. According to this, gross capital formation and labor force have presented positive integration while other variables showed the negative influence on economic growth during the provided time period in case of Brazil
Keywords: Brazil; Agriculture productivity; Economic growth